VOCs concentrations and emission rates in hospital environment and the impact of sampling locations - Hyttinen Marko; Rautiainen Paavo; Ruokolainen Joonas; Sorvari Jouni; Pasanen Pertti (TAYLOR & FRANCIS INC, 2022)
In this study, volatile organic compounds (VOCs) were measured from 47 hospital rooms to determine the most suitable sampling location for VOCs indoors. Another goal was to find out the most predominant VOCs and their emission per floor area in a hospital environment. Three samples were taken from each room simultaneously: one from the center of the room, one from the floor near the wall, and one from the exhaust air terminal. Concentrations of the VOCs were relatively low in all the cases, and the most abundant compounds were decamethylcyclopentasiloxane, d-limonene, xylenes, and 2-methyl-2-propanol. The average emission rates of the main compounds per floor area varied between 49 and 81 mu g/m(2)h. Statistical analyses showed that room area and volume affected differently the total volatile organic compounds (TVOC) concentrations among the sampling locations. Concentrations were higher at the exhaust air terminal than in samples at the floor and middle of the room. VOC levels were the same at the different sampling locations when the size of the room was below 10 m(2). However, field measurements and statistical analyses showed that when the size of the room increased, the most evenly distributed VOCs can be measured most reliably in the vicinity of the exhaust terminal device or in the exhaust air.